2003
DOI: 10.1074/jbc.m212973200
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of N- and C-terminal Determinants in the Activation of the Kv2.1 Potassium Channel

Abstract: The human and rat forms of the Kv2.1 channel have identical amino acids over the membrane-spanning regions and differ only in the N-and C-terminal intracellular regions. Rat Kv2.1 activates much faster than human Kv2.1. Here we have studied the role of the N-and C-terminal residues that determine this difference in activation kinetics between the two channels. For this, we constructed mutants and chimeras between the two channels, expressed them in oocytes, and recorded currents by two-electrode voltage clampi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
71
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 28 publications
7
71
0
Order By: Relevance
“…Schulteis et al (31) showed that exposure of cells expressing Kv1.1 to oxidizing conditions causes the formation of a disulfide bond between a cysteine in the N-terminal T1 domain and a cysteine in the C terminus of the adjacent subunit. Also, an interaction between the N terminus and the C terminus of Kv2.1 is responsible for the gating process (32)(33)(34). Furthermore, an interaction between the N terminus and the C terminus of TRPV5 has been identified by a GST pull-down assay and coimmunoprecipitation (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schulteis et al (31) showed that exposure of cells expressing Kv1.1 to oxidizing conditions causes the formation of a disulfide bond between a cysteine in the N-terminal T1 domain and a cysteine in the C terminus of the adjacent subunit. Also, an interaction between the N terminus and the C terminus of Kv2.1 is responsible for the gating process (32)(33)(34). Furthermore, an interaction between the N terminus and the C terminus of TRPV5 has been identified by a GST pull-down assay and coimmunoprecipitation (28).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the functional results obtained with the chimeras [N-IVT4]T6, [N-VIT4]T6, and [CT4]T6 suggest that the interaction between the N terminus and the C terminus is not absolutely required to assemble a functional TRPC channel. However, this interaction may be involved in the regulation of the activity of the channel, as is the case for Kv2.1 (32). Another possibility is that different assembly phases must occur to get the functional conformation of the channel.…”
Section: Discussionmentioning
confidence: 99%
“…They also participate in channel assembly in Kv 2.1 (13,14). All members of the Shaker subfamily of Kv channels display a remarkable amino acid sequence conservation within the distal region of their C termini, characterized by the -T͞SDV motif (10,12).…”
mentioning
confidence: 99%
“…Furthermore, Ju et al (14) have recently proposed that the gating of the Kv2.1 channel is strongly influenced by specific interactions between the N-and Cterminal domains, suggesting they do assume a well defined 3D structure. Finally, the 3D structure of the full-length Shaker potassium channel ␣-subunit at 25-Å resolution (17) revealed a larger membrane-embedded domain and a smaller cytoplasmic domain, conjoined by four thin connectors resembling a ''hanging gondola'' (18).…”
mentioning
confidence: 99%
“…Amino acids 67 and 75 of the N-terminal T1 domain and amino acids 740 -853 of the C-terminal region ("CTA" domain) have been shown to be involved in determining the time course of activation of the channel (19), and interactions between the T1 domain and the CTA domain have been demonstrated. We report here that relative voltage-gated rearrangements in the cytoplasmic domain of the K v 2.1 channel may be successfully probed by FRET between ECFP and EYFP fluorophores fused to the termini of the K v 2.1 monomers.…”
mentioning
confidence: 99%